Valuing local public goods with advanced stated preference models: Traffic calming schemes in Northern England - Riccardo Scarpa; Guy D. Garrod; Kenneth G. Willis (Fondazione Eni Enrico Mattei (FEEM), 2001)
The paper reports the results of three stated preference surveys in urban-rural areas in Northern England. The objective is that of valuing the economic benefits from traffic calming schemes in two areas with different traffic problems from stated preference observations. Both choice-experiments and contingent valuation methods are employed using advanced modelling. Fixed and random coefficient utility models are estimated from responses of the choice-experiments, while double-bound spike models are used for contingent valuation. Welfare estimates from the different methods are compared. The role of accounting for repeated choices is found to be of relevance. Choice modelling is designed to disentangle the values of benefits from 5 major attributes of traffic calming schemes (noise abatement, speed control, community severance, aesthetic layout and tax burden).
Keywords: 330; Local public goods; non-market valuation; stated preference; choice experiments; traffic calming; Lokale öffentliche Güter; Bewertung; Willingness to pay; Multikriteria-Verfahren; Verkehrsberuhigung; England (Nord)